The Impact of Competition and Allelopathy on the Trade-Off between Plant Defense and Growth in Two Contrasting Tree Species - Fernandez, Catherine; Monnier, Yogan; Santonja, Mathieu; Gallet, Christiane; Weston, Leslie A.; Prévosto, Bernard; Saunier, Amélie; Baldy, Virginie; Bousquet-Mélou, Anne (Frontiers in Plant Science, 2016)
In contrast to plant-animal interactions, the conceptual framework regarding the impact of secondary metabolites in mediating plant-plant interference is currently less well defined. Here, we address hypotheses about the role of chemically-mediated plant-plant interference (i.e. allelopathy) as a driver of Mediterranean forest dynamics. Growth and defense abilities of a pioneer (Pinus halepensis) and a late-successional (Quercus pubescens) Mediterranean forest species were evaluated under three different plant interference conditions: i) allelopathy simulated by application of aqueous needle extracts of Pinus, ii) resource competition created by the physical presence of a neighboring species (Pinus or Quercus), and iii) a combination of both allelopathy and competition. After 24 months of experimentation in simulated field conditions, Quercus was more affected by plant interference treatments than was Pinus, and a hierarchical response to biotic interference (allelopathy < competition < allelopathy + competition) was observed in terms of relative impact on growth and plant defense. Both species modulated their respective metabolic profiles according to plant interference treatment and thus their inherent chemical defense status, resulting in a physiological trade-off between plant growth and production of defense metabolites. For Quercus, an increase in secondary metabolite production and a decrease in plant growth were observed in all treatments. In contrast, this trade-off in Pinus was only observed in competition and allelopathy + competition treatments. Although Pinus and Quercus expressed differential responses when subjected to a single interference condition, either allelopathy or competition, species responses were similar or positively correlated when strong interference conditions (allelopathy + competition) were imposed.